Synthesis and characterization of a starch-based cationic flocculant for microalgae harvesting - Yanling, Cheng; Wei, Hua; Wenhui, Liu; Wanqing, Wang; Xiao, Ye; Liang, Li; Chen, Paul; Ruan, Roger (International Journal of Agricultural and Biological Engineering, 2016)
A process for making a starch-based cationic flocculant for microalgae harvest was studied and the performance of the flocculant was evaluated. The substituted cationic starch was prepared by reacting corn starch with glycidyltrimethylammonium chloride (GTAC), during which the hydroxyl groups of anhydroglucose units of the starch were partially substituted by the ammonium groups through etherification. The factors affecting degree of substitution (DS), such as reaction temperature and time, catalyst amount, and the water content were investigated and optimal reaction conditions were determined. The relationship between DS and microalgae harvest was determined. A batch of cationic starch with optimal DS was synthesized and used for flocculation experiments. The flocculation experiment results showed that, for the original microalgae concentration (dry weight) of 1 g/L, the cationic starch-based flocculants can harvest over 90% of the microalgae in pH from 5 to 10, with the aggregation and precipitation time of 10 min to 30 min, and the mass ratios of flocculants to microalgae of 1:8-1:18 (dry mass ratio). Using starch-based flocculant to harvest microalgae in the effluent is not only efficient, but also nontoxic to the water system, which is very important to the effluent reuse and certain microalgae applications.Keywords: microalgae, harvest, flocculation, starch-based cationic flocculantsDOI: 10.3965/j.ijabe.20160903.2049Citation: Cheng Y L, Hua W, Liu W H, Wang W Q, Ye X, Li L, et al. Synthesis and characterization of a starch-based cationic flocculant for microalgae harvesting. Int J Agric & Biol Eng, 2016; 9(3): 139－145.